Targeted information and sustainable consumption: Field evidence - Loukas Balafoutas; Esther Blanco; Raphael Epperson (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2024)
Technological progress offers new and promising ways to provide targeted information to consumers and facilitate behavioral change. We conduct a randomized controlled trial with a global supermarket chain and food producer to evaluate the effectiveness of a targeted information intervention that offers consumers individualized feedback about the sustainability of purchased products and close substitutes. We find that the majority of consumers access the information, independently of whether they have bought sustainable or unsustainable products in the past. Yet, providing the targeted information has no significant impact on consumption choices, which is neither driven by inattention to information nor price differentials.
Keywords: D12; D82; Q53; 330; Information provision; pro-environmental behavior; sustainability; label credence goods; randomized controlled trial